EXPERIMENTAL INVESTIGATION OF FLOW PATTERN AROUND REPELLING AND ATTRACTING T-HEAD SPUR DIKES ON FLAT BED - Mahdieh Najafabadi, A.; Bateni, M. M. (University of Eloued جامعة الوادي, 2017)
Use of T-head spur dikes is one of the common methods to control erosion of riverbanks. Nevertheless, setting spur dikes in the flow direction leads to modification of flow path and local scour in the site of the spur dike. In case of intensification, this can destruct the structure and the riverbank. Therefore, understanding its mechanism and characteristics are crucial. The main objective of this study is to investigate and compare the flow pattern around submerged attracting and repelling T-head spur dikes in a flat bed. The experimental Flume was a rectangular channel with bed width of 92 cm, bank height of 60 cm and length of 8.7 m. around spur dike at 24 cross sections, 16 profiles and 3 depths velocity was measured by 2-D electromagnetic velocimeter. The results showed that downflow in upstream of repelling spur dike is stronger than the downstream part and the Length of downstream circulation zone is larger in attracting spur dike.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 03
Keywords: T-head spur dike; repelling spur dike; attracting spur dike; flat bed